Analisis Tingkat Kebisingan Kampus Mesen Universitas Sebelas Maret Terhadap Kepadatan Jalan Jendral Urip Sumoharjo - Luthfia; Rida Ayu Surya Putri; Mario Pintor David Simanjutak; Siti Rachmawati; Wian Ayu Wardha’adlina (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2024)
The university, one of the primary channels for the transfer of information, is heavily influenced by several outside forces. It is well-recognized that noise can interfere with learning and teaching, upsetting and distracting pupils in the process. This investigation aimed to gauge the noise intensity and plot its dispersion across Sebelas Maret University's Mesen Campus. This study was carried out at the Mesen Campus of Sebelas Maret University. Using a sound level meter and the GPS Essentials application to create waypoints for the research locations, the data collection and measurement method is carried out directly in the field with a quantitative approach for 10 minutes at each place. The measurement time is conducted during the course of the 9-hour activity at regular intervals between 08.30 and 17.30, with a measuring distance every three hours in the morning, afternoon, and evening. Descriptive data analysis was done on the collected information by comparing the value Leq, and the noise quality criterion. Noise mapping using the Surfer software. The findings revealed that the noise level at the FSRD's entrance was 90.37 dB(A), that it was 81.45 dB(A) in front of the FSRD class, 78.35 dB(A) in the middle of the field, and that it was 55.57 dB(A) in front of the vocational school. The noise level surpasses the quality standard established by the government in KEP-48/MENLH/11/1996 regarding the Noise Level Standard for School Activities or the Like, which is 55 dB(A), according to all of the data. Due to the increased amount of highway activity, the four points' noise levels are at their maximum between 16:30–17:30 in the afternoon.